Variations in plume activity reveal the dynamics of water-filled faults on Enceladus - Souček, Ondřej; Běhounková, Marie; Lanzendörfer, Martin; Tobie, Gabriel; Choblet, Gaël (Nature communications, 2024)
After discovering a jet activity near the south pole of Saturn's moon Enceladus, the Cassini mission demonstrated the existence of a subsurface water ocean with a unique sampling opportunity through flybys. Diurnal variations in the observed brightness of the plume suggest a tidal control, although the existence and timing of two activity maxima seem to contradict stress analysis predictions. Here, we re-interpret the observed plume variability by combining a 3D global model of tidal deformation of the fractured ice shell with a 1D local model of transport processes within south-polar faults. Our model successfully predicts the observed plume's temporal variability by combining two independent vapour transport mechanisms: slip-controlled jet flow and normal-stress-controlled ambient flow. Moreover, it provides a possible explanation for the differences between the vapour and solid emission rates during the diurnal cycle and the observed fractionation of the various icy particle families. Our model prediction could be tested by future JWST observations targeted when Enceladus is at different positions on its orbit and could be used to determine the optimal strategy for plume material sampling by future space missions.